ANALISIS PRODUCT POSITIONING PEMUTIH WAJAH POND’S FAIR & LOVELY DI SURABAYA - Rina Dewi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2018)
This research examined about product positioning analysis of X face bleach in Surabaya. The growing competition in the cosmetic whitening business needs to get the attention of PT Unilever as the licensee of X brand to do the positioning for its brand in face bleaching product category to face the competition. The existence of a society that over communications, the company must create a position in the minds of prospects. Companies should create products with important attributes in accordance with the consumer needs selected by the company, then communicated to consumers to form a perception or to get a response from consumers. According to Walker, Boyd & Larreche (1992: 203) that positioning can be done in two ways: physical product positioning and perceptual product positioning. One way to assess the current position of a product offered against a competitor is based on how the supply is compared to a set of objects, ie physical characteristics. For perceptual product positioning, consumers usually do not want to be bothered with information about the physical characteristics of the product, consumers do not buy physical products but they buy the benefits of the product. Consumers evaluate the product on the basis of what it does rather than what it is. The analysis model used in this study is a model adopted from "Steps in The Positioning Process" by Walker, Boyd & Larreche (1992: 208). The analytical technique used is the factor analysis suggested by Walker, Boyd & Larreche (1992: 227) which will generate perceptual mapping to find out each of the facial whitening brand positions under study. From the analysis result, a perceptual mapping image with two dimensions, which is a simplification of the six attributes that have high correlation with each other and has the same variant. Based on the results of the analysis, it turns out the first research hypothesis stating that the position of X has not been superior compared to its proven competitors. While the second research hypothesis that states the position of X not in accordance with the ideal brand (ideal brand) in terms of the attributes offered proven. It is characterized by the location of each brand on each dimension, the beautiful dimension (x axis) and the healthy dimension (y-axis). The location of the X coordinates is (0.34948; 0.51494) while the ideal position is point at (0.83076; 0.72247). Whereas from the six (6) brands examined closest to the ideal point is the brand Oil of Olay with coordinates (0,50162; 0,70537)